2014
DOI: 10.5121/ijmvsc.2014.5402
|View full text |Cite
|
Sign up to set email alerts
|

Criteria of Selecting Bank in Pakistani Banking Sector: Study of Banking Customers in Sahiwal, Pakistan

Abstract: This study is designed to evaluate the customer's behavior towards the bank selection in Sahiwal Division

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…It refers to the fact that customers are influenced by responsive attitude of the bank staff. The finding is consistent with the results reached by Hamid and Masood (2011) and Awan and Azhar (2014) and Zulfiqar et al (2014) who provided evidence that quality of service is the influential factor for the customer in IBs. However, the finding is inconsistent with the results reached by previous empirical studies that reported by Abduh and Omar (2012) who provided evidence that quality of service provided by bank staff play minor influence on customers in selecting IBs in Malaysia.…”
Section: Selection Criteriasupporting
confidence: 82%
See 1 more Smart Citation
“…It refers to the fact that customers are influenced by responsive attitude of the bank staff. The finding is consistent with the results reached by Hamid and Masood (2011) and Awan and Azhar (2014) and Zulfiqar et al (2014) who provided evidence that quality of service is the influential factor for the customer in IBs. However, the finding is inconsistent with the results reached by previous empirical studies that reported by Abduh and Omar (2012) who provided evidence that quality of service provided by bank staff play minor influence on customers in selecting IBs in Malaysia.…”
Section: Selection Criteriasupporting
confidence: 82%
“…Imtiaz et al (2013) revealed that customers choose an Islamic bank mostly due to two important factors namely religious motives and banking services. Zulfiqar et al (2014) pointed out that customers select bank according to bank convenience, quality services provided by the bank and the service charges. Awan and Azhar (2014) provided evidence that religion is considered at lower level in selection criteria of Islamic banking.…”
Section: Literature Review and Previous Studiesmentioning
confidence: 99%
“…For instance, customer satisfaction is the most critical concern for Islamic banking, as it is believed that if the customers are satisfied, it leads to more demand for the products that Islamic banking has to offer (Awan & Azhar, 2014). Many studies have found that a bank's location significantly affect the consumer's choice of banking (Amin, 2013;Marimuthu, Jing, Gie, Mun, & Ping, 2010;Ramadan, 2013;Rehman & Shabbir, 2010;Siddique, 2012;Zulfiqar et al, 2014). Some studies reported that a convenient location of a bank is an important determinant of the consumers' preferences when the choice of bank is in question (Holstius & Kaynak, 1995;Kaynak & Kucukemiroglu, 1992;Mokhlis, Mat, & Salleh, 2008).…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…The existing literature explores the conventional determinants for selecting the Islamic banking system. These determinants include low service charges, accessibility to bank branches, service quality, banks' overall reputation, and recommendations from family and friends (Awan & Azhar, 2014;Tara, Irshad, Khan, Yamin, & Rizwan, 2014;Zulfiqar, Arshad, Fareed, Shahzad & Hussain, 2014). This study used the Divine Economics approach, which argues that individuals having a belief in an afterlife, make their current life choices of commodities and services in accordance with their respective faith patterns (Hamdani, Ahmad, Khalid & Tahir, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Convenience and service provision are very important factors perceived by consumer (Ulaganathan, 2011). Similarly, Convenience, quality of services and price and cost are very important for bank selection in Sahiwal city which need to be keep in minds while making marketing strategy (Zulfiqar, Arshad, Fareed, Shahzad, & Hussain, 2014). The suggestion that the author gives is bank managers should provide internet banking, mobile banking and email banking for attracting and retaining young customers.…”
Section: Literature Reviewmentioning
confidence: 99%